2020
DOI: 10.1136/bmj.m2436
|View full text |Cite
|
Sign up to set email alerts
|

State handgun purchase age minimums in the US and adolescent suicide rates: regression discontinuity and difference-in-differences analyses

Abstract: ObjectiveTo evaluate the association between US state policies that establish age 18 or 21 years as the minimum purchaser age for the sale of handguns and adolescent suicide rate.DesignRegression discontinuity and difference-in-differences analyses.Setting46 US states without policy changes between 2001 and 2017; Missouri and South Carolina, which lowered the age for handgun sales in 2007 and 2008, respectively; and West Virginia and Wyoming, which increased the age for handgun sales in 2010.ParticipantsAdoles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…All mortality data is drawn from WHO [6]. The three civil forms of violent lethal whenever or wherever used and known to be associated with young adult suicides in the USA, [7][8][9][10][11]. Moreover, this link between suicide and easy access of guns has long been known to be associated with gun bearing occupations in other Western countries [18][19][20] made especially dangerous by the impetuosity of Youth.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…All mortality data is drawn from WHO [6]. The three civil forms of violent lethal whenever or wherever used and known to be associated with young adult suicides in the USA, [7][8][9][10][11]. Moreover, this link between suicide and easy access of guns has long been known to be associated with gun bearing occupations in other Western countries [18][19][20] made especially dangerous by the impetuosity of Youth.…”
Section: Methodsmentioning
confidence: 99%
“…Several American studies have shown that at State level there is a strong correlation between access to guns and deaths [9,[23][24]. Whilst in most American States eighteenyears old can legally purchase guns [10,25]. which reflects the fact that there are more guns in the USA than people-1205per 100,000…”
Section: Gun Ownershipmentioning
confidence: 99%
See 2 more Smart Citations
“…However, some of the policies with a meaningful demonstration of reducing adolescent suicide are state policies that promote safe firearm ownership and reduce access to those at risk of suicide. Higher minimum ages for firearm ownership and concealed carry (> 21), permit-to-purchase laws, minimum waiting periods for purchase, and child access prevention laws are associated with lower rates of adolescent suicide [ 97 99 ]. Many professional medical, surgical, and trauma societies support the implementation of such policies that have the potential to meaningfully reduce suicide through policies promoting safe firearm ownership [ 100 ].…”
Section: Advocating For Policies Demonstrated To Reduce Adolescent Te...mentioning
confidence: 99%